2023
DOI: 10.1007/s40273-023-01321-3
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Emerging Good Practice and Future Research in Relation to Family and Caregiver Health Spillovers in Health Economic Evaluations: A Report of the SHEER Task Force

Edward Henry,
Hareth Al-Janabi,
Werner Brouwer
et al.

Abstract: Background Omission of family and caregiver health spillovers from the economic evaluation of healthcare interventions remains common practice. When reported, a high degree of methodological inconsistency in incorporating spillovers has been observed. Aim To promote emerging good practice, this paper from the Spillovers in Health Economic Evaluation and Research (SHEER) task force aims to provide guidance on the incorporation of family and caregiver health spillovers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 79 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…For instance, inadequate folic acid intake by prospective mothers increases the risk of spina bifida in children [ 211 213 ], a condition that can result in a wide range of disabilities depending on the lesion’s location, often requiring extensive caregiving [ 214 , 215 ]. Caregivers of such children with disabilities, whether parents or other individuals, face various health-related problems [ 216 , 217 ], and it is recommended that caregiver costs and health consequences be included in economic evaluation from a societal perspective [ 48 , 49 , 218 ]. Studies have demonstrated that taking folic acid supplements before conception significantly reduces the risk of spina bifida [ 118 , 219 224 ], thereby preventing disabilities in children and eliminating the need for caregiving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, inadequate folic acid intake by prospective mothers increases the risk of spina bifida in children [ 211 213 ], a condition that can result in a wide range of disabilities depending on the lesion’s location, often requiring extensive caregiving [ 214 , 215 ]. Caregivers of such children with disabilities, whether parents or other individuals, face various health-related problems [ 216 , 217 ], and it is recommended that caregiver costs and health consequences be included in economic evaluation from a societal perspective [ 48 , 49 , 218 ]. Studies have demonstrated that taking folic acid supplements before conception significantly reduces the risk of spina bifida [ 118 , 219 224 ], thereby preventing disabilities in children and eliminating the need for caregiving.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that the total spillover QALY gains/losses for parents, family members, and others may be correlated with the size of the family and caregiving circle. Recently, an international task force was formed to provide guidance on the incorporation of family and caregiver health spillovers in cost-effectiveness and cost-utility analyses [ 218 ]. While the task force does not specifically provide recommendations for maternal-perinatal interventions, future researchers are encouraged to consult the SHEER Task Force recommendations on spillover effects when conducting CUAs for maternal-perinatal interventions.…”
Section: Discussionmentioning
confidence: 99%
“…While the potential for allocative justice to be jeopardised by consideration of health spillovers in economic evaluation has long been established Basu & Meltzer, 2005), recent commentaries on the normative implications of their inclusion (Brouwer, 2019;Dixon & Round, 2019;McCabe, 2019) have brought the need to investigate the possible distributional consequences of spillovers into sharp focus (Henry et al, 2023). Apart from an initial effort by Tubeuf et al (2019), who propose prioritisation of patient health via an equivalence scale-based approach, there is very little research on the extent, acceptability, or means of mitigation of the equity impacts of spillover inclusion identifiable in the literature.…”
Section: Health Spillovers In Health Economic Evaluationmentioning
confidence: 99%
“…Equation ( 1) highlights the differentially weighted spillovers specific to each network member, which may be of value in a decision-making context and in safeguarding transparency when including spillovers (Henry et al, 2023). It can, however, also be simplified 1 to give Equation (2), which reinforces that the total incremental spillover is independent of ranking.…”
Section: Overview Of Approachmentioning
confidence: 99%